Efektivitas Senam Otak dalam Meningkatkan Hafalan Al-Qur’an pada Siswa SMP-IT Ash-Shidiqi di Kecamatan Pemayung - Faridah Faridah; Ariyanto Ariyanto (Jurnal Akademika Baiturrahim Jambi, 2021)
Concentration of learning is an effort to focus the mind or attention to a subject that is being studied and to memorize the Al-quran by setting aside other things that have nothing to do with what is being studied. There are some students who are easy to accept the lessons / memorize al-quran, and otherwise, there are several students too who have difficulty. Ash-Shidiqi Integrated Islamic Junior High School is a school that refers to the education office curriculum and the Indonesian Integrated Islamic School Curriculum with the flagship program Quantum Tahfizh, but in practice many students find it difficult to concentrate on memorizing Al-Qur'an. The results of interviews with students Ash-Shidiqi Integrated Islamic Junior High School, it is difficult to focus on their concentration in memorizing  Al-qur'an because the school environment is not conductive, this is beside the according with the observations of researchers that many students are looking for a place to be alone in memorizing Al-qur 'an and sometimes students was found  themselves to covering their heads with a bag to concentrate on memorizing. This type of research is quasi experimental (pseudo experiment). This study design had a control group, but it was not selected by randomly. In this study the researchers used two groups, namely the treatment group who were given brain exercise with a frequency of 6 times a week, light intensity, with duration of 1 exercise. The results showed that in the pre-test and post-test intervention groups there was p = 0.008 or p <0.05. It means that there are significant differences in the ability to memorize before and after being given brain exercise. Whereas in the control group p = 0.063 or p> 0.05 that means there is no significant difference between the pre-test and post-test results because they are not given brain exercise. This research is expected to make a good contribution to Ash-Shidiqi Integrated Islamic Junior High School in implementing the Quantum Tahfizh Program and will provide input in preparing the SMP-IT school program based on tahfizh al-quran